PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS REFUTATION TEXT PADA MATERI SENYAWA HIDROKARBON DI SMA NEGER 3 PONTIANAK - Wahyuni, Neri; Muharini, Rini; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aims of this study were to determine the validity of refutation text-based chemistry worksheet on material hydrocarbon  and to measure student?s  response. The form of this research was research and development (R & D) that adapted from the Four D (4D) model. The subject of this study was refutation text-based chemistry worksheet which was on 10 and 37 students of SMAN 3 Pontianak at the initial trial and main trial respectively. Data collection instruments used were validity assessment sheets and studeny?s response questionnaire. The results of data processing showed that material aspect gave 90.0%, language aspect gave 85.2%, and graphic aspect gave 87.4%. Based on student?s response questionnaire, the response  result in the initial trial and in the main trial were 88.1% and 86.7% respectively. These datas showed  that student?s response to refutation text-based chemistry worksheet was classified as very high category. Keywords:  Chemistry Worksheet, Refutation Text, Hydrocarbon Compound